CT in pediatric trauma patients: review = CT-Diagnostik bei Kindern und Jugendlichen im Schockraum - Appelhaus, Stefan; Schönberg, Stefan; Weis, Meike (RöFo, 2025)
The decision as to whether to perform a computed tomography (CT) examination in severe pediatric trauma poses a challenge. The therapeutic benefit of computed tomography in injured children is lower compared to adults, while the potential negative effects of ionizing radiation may be higher. Thus, the threshold for CT should be higher. Centers that less frequently treat pediatric cases tend to conduct more whole-body CT examinations than dedicated pediatric trauma centers, indicating a clinical overestimation of injury severity with subsequently unnecessary imaging due to inexperience. On the other hand, a CT scan that is not performed but is actually necessary can also have negative consequences if an injury is detected with a delay. An injured child presents a challenging situation for all involved healthcare providers, and thus requires a structured approach to decision-making. Selective literature review of the benefits and risks of CT in injured children, as well as indications for whole-body and region-specific CT imaging. This article provides an overview of current guidelines, recent insight into radiation protection and the benefits of CT in injured children, and evidence-based decision criteria for choosing the appropriate modality based on the mechanism of injury and the affected body region.
Artikel online veröffentlicht: 29. Juli 2024
Gesehen am 12.11.2024